Penggunaan Aplikasi CIKO SMART sebagai Sarana Pengaduan Masyarakat - Pamesti, Rere Cika Ihza (Advances in Police Science Research Journal, 2019)
This research was written on the basis of a breakthrough given by the Cirebon City Police in relation to increasing public service in the form of a release in January 2019, an integrated application that presents various features in a package called CIKO SMART. In this CIKO SMART application there are various features that are presented, and researchers focus their research on community complaint features. However, until July 2019 there were fewer than 20 complaints submitted, and none of them had been followed up by the Cirebon City Police, so that they were judged not to be in line with the purpose of the innovation. Therefore, a study was conducted aimed at finding out the use of the CIKO SMART application, as well as the influencing factors. This research was conducted with a qualitative approach, the type of research conducted was field research, as well as data collection techniques using interviews, observation, and document review. Data validity uses source, time, and technique. Data presentation uses data reduction, data presentation, and drawing conclusions. The results of the study found that the use of the CIKO SMART application to date for the system, implementing operators, supervision, number of implementers, and socialization did not meet the standards. The influencing factors are classified into two, namely supporting and inhibiting. For supporting factors, namely the presence of leadership policies, a good work culture, and high expectations from the community in the use of police technology. The inhibiting factor itself comes from inadequate human resources, lack of community knowledge, networks, and devices that do not meet standards. Based on the results of research that has been done, the authors suggest providing vocational education to operators, enforcing standart operational procedure, expanding platforms, increasing socialization to the public using social media.